Systemic cytokine and chemokine responses in immunized mice challenged with staphylococcal enterotoxin B. (July 2017) - Hudson Reichenberg, Laura C.; Garg, Renu; Fernalld, Raymond; Bost, Kenneth L.; Piller, Kenneth J.
Abstract: The cytokine storm induced by staphylococcal enterotoxin B (SEB) describes the rapid and dramatic induction of mediators which are likely responsible for the toxin's deleterious effects. However despite the use of numerous animal models for investigating SEB related illness in humans, mechanisms of toxicity and correlates of protection remain unclear. In the present study, we used an LPS-potentiated model of SEB lethality to investigate the toxin-induced cytokine and chemokine responses in untreated and immunized mice. Of 30 separate mediators analyzed, serum levels for 28 or 27 of these cytokines and chemokines were elevated following administration of dosages of 3 or 30 LD50 of native SEB, respectively. Mice immunized with a non-toxic SEB vaccine candidate expressed in either E. coli or transgenic soy expression systems were protected from lethality when challenged with potentiated SEB. The majority of SEB-induced cytokines and chemokines (21 of 28 or 23 of 27 following challenge with dosages of 3 or 30 LD50 of native SEB, respectively) were significantly decreased in mice immunized with an SEB vaccine candidate when compared to control animals. Together, these studies provide the most comprehensive evaluation of the cytokine storm induced in this LPS-potentiated model of SEB lethality to date. As with other animal models, the identification of those mediators which are necessary and sufficient for SEB-induced toxicity remains unclear. Highlights: Most comprehensive chemokine and cytokine profile in a mouse model of staphylococcal enterotoxin B toxicity to date. Immunizing with a vaccine candidate protects mice and reduces selected toxin induced chemokine and cytokine production. Despite this comprehensive profiling effort, identifying mediators necessary and sufficient for toxicity remains unclear.